The Effect of Rubber Prices and Production on the Income of Rubber Farmers in North Padang Lawas Regency - Permatasari Siregar, Indah (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
The aim and discussion of this research is to determine the influence of prices and labor absorption on latex production on the welfare of the people of Pengirkiran Village, North Padang Lawas Regency. Research data is primary data obtained directly from the first source, either from individuals, such as the results of filling out a questionnaire. This research uses a quantitative descriptive approach with a secondary data analysis (ADS) approach using multiple linear regression analysis methods assisted by SPSS (Statistical Package For Social Science) software 22. The results of the research conducted show that (1) rubber prices have a positive and significant effect on farmers' welfare rubber in Halongonan District, North Padang Lawas Regency. (2) Rubber production has a positive and significant effect on the welfare of rubber farmers in Halongonan District, North Padang Lawas Regency. (3) Rubber prices and production have a significant effect on the welfare of farmers in Halongonan District, North Padang Lawas Regency.